Gender focused training and knowledge enhances the adoption of climate resilient seeds - Dar, Manzoor H.; Waza, Showkat A.; Nayak, Swati; Chakravorty, Ritadhi; Zaidi, Najam W.; Hossain, Mosharaf (Elsevier, 2020)
Adoption of any agricultural technology depends upon the way in which farmers are being informed about its benefits. Educational status, caste, gender and other social issues also play a significant role in the adoption process. To evaluate the impact of trainings on quality seed production, access to the climate resilient rice seeds, availability of information about seed sources and use of IRRI super bags, a randomized experimental research was carried out over a period of two years across five different states of India. The baseline and a follow-up survey was conducted to capture the farming practices followed by during wet seasons of 2016 and 2017, respectively. The impact of trainings, seed use, information given and agro-based goods was evaluated by comparing the adoption behaviour of treatment and control farmers. There was an increase (28.8%) in the practice of using salt solution to clean seeds primarily due to the impact of quality seed production (QSP) trainings. Female farmers responded more than the male farmers as number of women adopting the practice was higher than men. The impact of the trainings on farmers' knowledge and adoption of climate resilient/stress tolerant rice varieties (STRV) was also more pronounced on females than on male farmers. Farmers’ access to seeds substantially enhanced the adoption and reusability irrespective of the gender. Similarly, the information delivered to the farmers was quite economical in enhancing the awareness and adoption of climate resilient rice, but the effect was predominantly driven by female farmers. Female farmers performed relatively better with respect to the storing the new seeds in IRRI super bags. Thus, incentivising farmers in general and female farmers in particular can serve as a potential means to adopt agricultural technologies that have potential to boost rural economy and enhance the food security. The results are being supported by a rigorous empirical analysis.